Model Model Restorasi Mall Berbasis Biofilia Sebagai Pusat Gaya Hidup Baru Konsumen Metropolitan - Purwanto Purwanto; Erlyna Hidyantari; Hardiono Hardiono (Ecobuss, 2020)
The purpose of the present study was to test the design consistency of modern retailing or malls with the concept of biophilia. Building on the attention restoration theory (ART), the researchers used four sub-dimensions of being away, extent, fascination, compatibility to serve as variables that illustrate the potential of restoration of malls as the center of a new lifestyle of metropolitan consumers in the digital era. The present study used a sample of 120 respondents in the city of Surabaya, East Java. The research method used a 2 x 2 experimental design with the MANOVA and ANOVA methods in two experimental studies. Study 1 found that, as a whole, consumers regarded the lifestyle center of nature nuances as more likely to be comfortable, relative to those consumers not seeing plants, and experienced three of the four environmental characteristics (sub-dimensions) that represent the restorative environment. Study 2 found no significant differences between shopping purposes and the four sub dimensions that served as the dependent variables.